Unbiased estimates of long‐term net survival of solid cancers in France1. Issue 10 (18th January 2013) - Jooste, Valérie; Grosclaude, Pascale; Remontet, Laurent; Launoy, Guy; Baldi, Isabelle; Molinié, Florence; Arveux, Patrick; Bossard, Nadine; Bouvier, Anne‐Marie; Colonna, Marc; ,
Abstract In cancer studies, net survival (observed if cancer was the only cause of death) is a useful indicator but survival estimation at 5 years is insufficient for planning healthcare needs. We estimated the net survivals at 5 and 10 years in a cohort of 387, 961 patients who had solid tumors between 1989 and 2004 and were followed‐up until January 1, 2008. The cases were actively followed‐up. Net survival was estimated with the unbiased Pohar‐Perme method. The standardized net survival used the international cancer survival standard weights. In men, the standardized net survivals ranged from 92% at 5 years and 89% at 10 years (testis) to 6% at 5 years and 5% at 10 years (pancreas). In women, it ranged from 91% at 5 years and 88% at 10 years (thyroid) to 10% at 5 years and 7% at 10 years (pancreas). The most frequent cancers had the highest net survivals: 84% at 5 years and 71% at 10 years for prostate and 84% at 5 years and 74% at 10 years for breast cancer. Advanced age was associated with poorer prognosis. In most cancers, the net survivals at 5 and 10 years increased over periods of diagnosis. Net cancer survival is unaffected by mortalities due to other causes. It is the only indicator suitable for comparisons between countries or periods of diagnosis within a given country. The 10‐year net survival confirmed the persistent unfavorable role of age in prognosis and the general improvement of cancer management over the last decade.